Feasibility of Booklet the Role of Biodiversity Based on Inventory of Post-Birth Medicinal Plant - Pertiwi, Kharisma Ananda; Panjaitan*, Ruqiah Ganda Putri; Wahyuni, Eko Sri; Lestari, Liya Angga (Jurnal IPA & Pembelajaran IPA, 2025)
Learning media is a tool used in the school that can help teacher in the teaching process. Media that is made according to needs can help students achieve learning goals effectively and efficiently. This research aims to determine the feasibility of booklet the role of biodiversity based on inventory of post-birth medicinal plants in Mekar Sari Village on the sub-material role of living things for life in class X. This study uses research development by Sugiyono which consists of determining potential and problems, data collection, designing media, validating, finally revising the design. The validity of the booklet media was obtained through content validation carried out by five validators. Booklet media validation is viewed from three aspects, namely format, content and language. Validation analysis refers to Lawshe (1975), namely content validity ratio (CVR) and content validity index (CVI). The research results show an average CVR of 1.00 and resulting in a CVI of 1.00 in the valid category. The results of the analysis in this research can be concluded that booklet media is suitable for use as learning media